La entrevista telefónica (2003)
ABSTRACT: If the objectives and requirements of the sounding have lead the investigator to that it believes that the best primary source of information is going to him to provide, not only the direct observation of certain events, but the verbal testimonies that a set of people provides who have participated or been present at these events, then the appropriate technique will be the telephone interview. These can be used in short opinion polls with determined public, that they have in any case, telephone.